EFISIENSI BEBERAPA JENIS TUNGKU KAYU BAKAR - Nurmala Hudaya; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1984)
The Forest Product Research and  Development Centre, Bogor, has  constructed  the Lorena,   Singer and the Traditional  fuelwood stoves to measured the  efficiency of each type. The material used for the construction of the stoves are clay, sand, sawdust, red-bricks  and  water.The  efficiency of  each  type  is  measured  by  using  the  stoves  for  cooking  water  to  boiling point in an aluminium pan, where rubber (Hevea brasiliensis) wood is used as fuelwood.The  stoves  efficiency is expressed  as the  ratio  between  the effective  heat the boiled  water absorbs and the potensial heat  produced by  firewoods.The results of the  observations and  calculations  of  the  efficiency of   the  respective types   of   firewood   stoves indicated  that  the  Lorena  stove  has the  highest  efficiency of  24.75%,  followed by the Singer stove with  24.50%, and the traditional  one,  the least  efficient   is 18.64%. Compared  with  the tested  traditional stove, the  Lorena  and  the  Singer stoves  appear  to have high efficiency which consumed 30% less of  fuelwood.